Az anya és a nyelv: Az Esti Kornél harmadik fejezetének biopoétikai összefüggéseiről - Balajthy, Ágnes (Studia Litteraria, 2023)
The third chapter of Kosztolányi’s volume of short stories is often considered to be a coming of age story, in which the eighteen-year-old protagonist’s train journey symbolizes his transformation from a child into an autonomous and independent subject. My interpretation attempts to undermine this reading through exploring the various roles family relations play in the narrative. Although Esti leaves his biological mother behind in the beginning of his adventure, I argue that his story remains centred around the of image of the mother(s); he is surrounded by mother figures and figurations of maternity. Via presenting the mouth simultaneously as an organ of eating, feeding, speaking, and kissing, Kosztolányi’s writing explores the intimate, corporeal, somatic aspect of language shared by the mother and the child. However, the frequent references to school, classical authors and foreign tongues (Latin, Greek, Italian, French) also display language as an external medium of reading, writing and memorizing. ese two aspects – in parallel with the biological and metaphorical understandings of motherhood – turn out to be inseparable in Kosztolányi’s work.